(untitled) (Economics and region, 2019)
According to the authors of the article, the creation of a specific structure for anti-crisis management should depend on the volume of activity and size of the enterprise, as well as the phases of the crisis: light, deep, catastrophe. As a result of this study, the authors found that the issues of organization planning of the company’s anti-crisis management services and the mechanism for its functional provision remain insufficiently investigated today. The principles considered by the authors on the proposed introduction to the anti-crisis management service argue that it should always be ready to overcome the crisis or critical pre-crisis situation that may arise due to a conflict of interests of the owners of enterprises in the market and the influence of factors of the internal and external environment.